Effect of Heat‐treatment on Accuracy of Infrared Spectroscopy and Digital and Optical Brix Refractometers for Measuring Immunoglobulin G Concentration in Bovine Colostrum. (27th December 2017) - Elsohaby, I.; McClure, J.T.; Dow, N.; Keefe, G.P.
Abstract : Background: Heat‐treatment of colostrum is a method developed to reduce calf exposure to pathogens. Infrared (IR) spectroscopy and Brix refractometers can be used for measuring colostral IgG concentration and assessing colostrum quality. Objectives: To determine the impact of heat‐treatment on accuracy of IR spectroscopy and Brix refractometers for measuring colostral IgG concentration and assessing colostrum quality before and after heat‐treatment. Animals: A total of 60 Holstein dairy cows on 8 commercial dairy farms. Methods: A cross‐sectional study was designed to determine the effect of heat‐treatment at 60°C and 63°C each for 30 and 60 minutes duration on colostral IgG concentration measured by the reference radial immunodiffusion (RID) assay, IR spectroscopy, and digital and optical refractometers. Results: Colostrum IgG concentration significantly decreased after heat‐treatment at 63°C for 30 or 60 minutes as measured by RID, but the IgG values remained unchanged when measured by IR spectroscopy and refractometers. The lowest correlation coefficient found between IR spectroscopy ( r  =   0.70) and RID results was in colostrum heat‐treated at 63°C for 60 minutes. For digital ( r  =   0.48) and optical ( r  =   0.50) refractometers, the lowest correlation coefficient was at 63°C for 30 minutes when compared to RID. The accuracy of the IR spectroscopy, digital and optical Brix refractometers was decreased from 91.7 to 80%, 81.7 to 45%, and 80 to 45%, respectively, when colostrum heat‐treated at 63°C for 60 minutes. Conclusions and Clinical Importance: Radial immunodiffusion, IR spectroscopy, and Brix refractometers exhibit utility for measuring IgG concentration when colostrum heat‐treated at 60°C but does not detect decrease IgG concentrations when heat‐treated at 63°C.